Development of electronic worksheet of biodiversity based on local wisdom and culture to enhance student’s learning motivation - Reni Ambarwati; Pinatri Wilujeng (Universitas Negeri Jakarta, 2023)
The Covid-19 pandemic has caused the teaching and learning process to be shifted to online learning. Many digital media that can be used for online learning. However, student learning motivation has decreased, even though many digital media can be used for online learning. Therefore, choosing good, effective, efficient, and attractive learning media is necessary. This research aimed to produce an electronic worksheet of biodiversity based on local wisdom and culture to enhance student’s learning motivation that is valid and practical. This research was used a 4D research model without a disseminate stage. The validity of electronic student worksheet was obtained from the validation results conducted by media experts, education experts, and material experts with validation instruments consisting of presentation, content, and language aspects. The practicality was obtained from teachers (n=5) and students (n=20) responses with response questionnaire instrument consisting of 20 statements, and student learning motivation questionnaire result with the ARCS model consisting of 9 statements. The data was analyzed descriptively and quantitatively. The result showed that the electronic student worksheet developed using the liveworksheets website obtained a validation score of 4 (very valid). Electronic student worksheet was declared practical with an average score from teachers 98% (very practical) and from students 96% (very practical). The results of the student learning motivation questionnaire using the ARCS model were 3.27 (very strong). Thus, it can be concluded that the electronic biodiversity worksheet based on local wisdom and culture to enhance student's learning motivation is valid and practical.